IMF Staff papers, Volume 37 No. 1. (IMF Staff Papers; IMF Staff Papers, 1990)
This paper examines factors affecting saving, policy tools, and tax reform. The literature on factors affecting saving and capital formation in industrialized countries is reviewed, and measurement problems are examined. The effect on the saving rate of real rates of return, income redistribution, allocation of saving between corporations and individuals, growth of public and private pension plans, tax incentives, the bequest motive, energy prices, and inflation is considered. The limited tools available to policymakers to affect savings are discussed.